2018
DOI: 10.1080/16549716.2017.1419033
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of genomics research in Africa: challenges and recommendations

Abstract: Background: There is exponential growth in the interest and implementation of genomics research in Africa. This growth has been facilitated by the Human Hereditary and Health in Africa (H3Africa) initiative, which aims to promote a contemporary research approach to the study of genomics and environmental determinants of common diseases in African populations. Objective: The purpose of this article is to describe important challenges affecting genomics research implementation in Africa. Methods: The observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 27 publications
1
49
0
Order By: Relevance
“…The available few GWAS revealed potential novel genetic biomarkers for antiretroviral and anti‐TB drug‐induced liver toxicities .The HLA‐C*04:01 allele is associated with nevirapine‐induced SJS/TEN in sub‐Saharan Africans . Currently, most genome‐wide single nucleotide polymorphism (SNP) arrays are designed for European ancestry, and the tag SNPs are less efficient for non‐Europeans, particularly for SSA populations . The lack of cost‐effective, high‐throughput genotyping technologies and microarrays with good SNP density coverage specific for African ancestry remains a challenge for the progress of PGx in Africa .…”
Section: African Pharmacogenomics Research Consortium: Focus On Hiv mentioning
confidence: 99%
See 1 more Smart Citation
“…The available few GWAS revealed potential novel genetic biomarkers for antiretroviral and anti‐TB drug‐induced liver toxicities .The HLA‐C*04:01 allele is associated with nevirapine‐induced SJS/TEN in sub‐Saharan Africans . Currently, most genome‐wide single nucleotide polymorphism (SNP) arrays are designed for European ancestry, and the tag SNPs are less efficient for non‐Europeans, particularly for SSA populations . The lack of cost‐effective, high‐throughput genotyping technologies and microarrays with good SNP density coverage specific for African ancestry remains a challenge for the progress of PGx in Africa .…”
Section: African Pharmacogenomics Research Consortium: Focus On Hiv mentioning
confidence: 99%
“…Currently, most genome‐wide single nucleotide polymorphism (SNP) arrays are designed for European ancestry, and the tag SNPs are less efficient for non‐Europeans, particularly for SSA populations . The lack of cost‐effective, high‐throughput genotyping technologies and microarrays with good SNP density coverage specific for African ancestry remains a challenge for the progress of PGx in Africa . Over the past two decades, PGx research in Africa has generated ample knowledge on variant alleles that determine patient variability in the plasma exposure and treatment outcome of drugs used to treat HIV, TB and malaria.…”
Section: African Pharmacogenomics Research Consortium: Focus On Hiv mentioning
confidence: 99%
“…Given the importance of Africa to studies of human origins and disease susceptibility (Gurdasani et al, ), there is exponential growth in the interest and implementation of genomics research in Africa which has been facilitated by the Human Hereditary and Health in Africa (H3Africa) initiative. The aim of H3Africa is to promote a contemporary research approach to the study of genomics and environmental determinants of common diseases in African populations (Adebamowo et al, ). Health care benefits greatly from the unprecedented and ongoing work elucidating the genetic/genomic basis of health, illness, disease risk, and treatment response (Calzone et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The Human Heredity and Health in Africa initiative is undertaking the ethics review process for genomic studies across Africa. A recent report on the challenges faced by this initiative suggested that the main barrier to ethics approval is a lack of genomic expertise within ethics committees . With increasing international data sharing efforts, internationally compatible solutions to research ethics issues need to be developed.…”
mentioning
confidence: 99%
“…A recent report on the challenges faced by this initiative suggested that the main barrier to ethics approval is a lack of genomic expertise within ethics committees. 5 With increasing international data sharing efforts, internationally compatible solutions to research ethics issues need to be developed. The Global Alliance for Genomics and Health has developed an ethics review recognition policy, 6 and Australia could continue to demonstrate leadership internationally if 442 remaining challenges to multijurisdictional research were addressed.…”
mentioning
confidence: 99%